Politeness Strategies by Logan Paul and Mike Ajlak in THE DONALD TRUMP INTERVIEW – IMPAULSIVE EP. 418 - Raffael Avriellio Khotania (Institute of Research and Community Outreach - Petra Christian University, 2025)
This qualitative study examines the politeness strategies used by Logan Paul and Mike Ajlak in The Donald Trump Interview – IMPAULSIVE EP. 418. Using Brown and Levinson’s (1987) theory as cited in Watts (2003), it focuses on spoken utterances directed specifically at Donald Trump. The data consists of utterances by Paul as the main host and Ajlak as the co-host. The findings show that both use more positive politeness strategies. Paul applies all four main politeness strategies, including bald on record, while Ajlak uses only three: positive politeness, negative politeness, and off record. Although both use these three strategies, they differ in the specific sub-strategies applied within each category. They also share some unused strategies. Their roles influence how they use these strategies: Paul leads the conversation, while Ajlak supports it. Despite the differences, both remain polite, especially considering their guest is a former president. The study concludes that they apply different strategies based on their roles. Further research on politeness in political interviews is recommended.